Study on factors affecting the petro physical properties of sandstone and conglomerate reservoirs of Baikouquan Formation, Junggar Basin - Kuang, Hao; Liu, Hao; Tan, Xianfeng; Yu, Jingwei; Song, Haiqiang; Zhou, Runchi; Wang, Junmin; Liu, Fei (Frontiers in Earth Science, 2023)
In recent years, with the fine oil and gas exploration of the Baikouquan Formation in the northwestern margin of the Junggar Basin, major breakthroughs have been made in oil and gas exploration. Sandstone and conglomerate reservoirs are developed in the Baikouquan Formation in this area, but the factors affecting the differences in petrophysical properties of these two types of reservoirs are still unclear. Taking the Baikouquan Formation in the Hongcheguai area on the northwestern margin of the Junggar Basin as an example, a large number of core observations, thin sections, scanning electron microscopy, and petrophysical property test data were used to evaluate the petrological characteristics, reservoir space types, diagenesis and pore evolution of the sandstone and conglomerate reservoirs. The results show that the sandstone and conglomerate of the Baikouquan Formation in the study area have a large content of tuffaceous components. The sandstone reservoirs are dominated by primary intergranular pores, and the conglomerate reservoirs are dominated by secondary dissolved pores. In addition, the porosity and permeability of the conglomerate of the Baikouquan Formation have a negative correlation, that is, as the porosity increases, the permeability gradually decreases. However, the porosity and permeability of sandstone reservoirs have a positive correlation. According to diagenesis analysis, compaction and cementation damage the petrophysical properties of the reservoir to a greater degree. Dissolution improves the petrophysical properties of sandstone reservoirs to a small extent, while improves that of conglomerate reservoirs to a greater extent. Moreover, local fractures are important factors affecting the petrophysical properties of conglomerate reservoirs. The existence of abnormal high pressure has a certain effect on the preservation of primary pores. On the whole, the controlling factors of the petrophysical properties of the conglomerate reservoirs in the Baikouquan Formation include sedimentation, diagenesis, and tectonic activies, while that of the sandstone reservoirs mainly include sedimentation and diagenesis.